Molecular Docking of Red Betel Leaf Bioactive Compounds (Piper crocatum) as Lipoxygenase Inhibitor - Fernanda Chairunisa; Mega Safithri; Dimas Andrianto; Rini Kurniasih; Riyan Alifbi Putera Irsal (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Degenerative diseases occurred due to several risk factors that are directly related to inflammationwhich affected several diseases such as coronary heart disease (CHD) and diabetes. One of theinflammatory causative agents is leukotrienes produced by the lipoxygenase enzyme (LOX) so thatit takes anti-inflammatory drugs made from herbal plants. Red betel leaf (Piper crocatum) potentiallyinhibited the lipoxygenase enzyme because it contains potential phytochemical compounds suchas alkaloids, flavonoids, eugenol, saponins, and tannins. This research aimed to test the inhibitionof active compounds from extract and fractions of red betel leaves that have the best inhibition forlipoxygenase enzymes causing malondialdehyde formed through molecular docking simulations. Thisresearch used lipoxygenase enzyme as receptor (PRB code: 4NRE), C8E as natural ligand and activecompound from extract and fractions of red betel leaves as a ligand. The highest inhibition regarded toNandrolone phenylpropionate and Sofalcone ligand with -10.4 kcal/mol and -9.1 kcal/mol of affinityenergy. Amino acid residues that played a role in ligand and receptor interaction were HIS373 andHIS378. The receptor structure with the best ligands was declared stable based on molecular dynamicssimulations.